Genotyping Pattern of Staphylococcus aureus Isolated From Nasal Carriers Among Health Care Workers in Two Hospitals (Imam Sajjad and Shahid Beheshti) in Yasuj City Using Coa-Typing Method - F Gharibpour Jahanabad; Y Mahmoudi mourderaz; P Zanganeh; A Sharifi; M Naghmachi; S Hasanzadeh; SS Khoramrooz (Armaghane Danesh Bimonthly Journal, 2019)
Background & aim: Staphylococcus aureus can colonize a variety of body sites such as skin, coetaneous membrane and especially the anterior nares.  The coagulase gene (coa) typing is a technique in which the organism is typed based on the polymorphic region of the coa gene. The aim of the present study was to determine the coa based typing of S. aureus isolates from health care workers in two teaching hospitals in Yasuj city.